Constructivist Approach To Early Childhood Through Audio-Visual Learning Media - Rahmawati, Afifah Puri; Binsa, Ucik Hidayah; Setyowati, Eny (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
The constructivist approach to early childhood through audio-visual learning media involves the use of technology to help children build self-knowledge and understanding actively. Through audio-visual media, children can be involved in activities that stimulate their cognitive, sensory and motor skills. Thus, children can build their own knowledge through critical and constructive thinking processes. Qualitative methods are research approaches used to understand social phenomena in depth by focusing on context, meaning and subjective experience. This approach includes collecting and analyzing data in the form of text, images, or sound to.Â reveal the complexity and variation in human life. The findings of a constructivist approach in early childhood through audio-visual learning media show that the use of this technology can improve their learning process significantly. By utilizing audio-visual media, children can be involved in more active and enjoyable learning experiences so that this can help develop children's self-knowledge actively.